Abortion policies at the bedside: a response - Blackshaw, Bruce Philip (Journal of medical ethics, 2023)
Hersey et al have outlined a proposed ethical framework for assessing abortion policies that locates the effect of government legislation between the provider and the patient, emphasising its influence on interactions between them. They claim that their framework offers an alternative to the personal moral claims that lie behind legislation restricting abortion access. However, they fail to observe that their own understanding of reproductive justice and the principles of medical ethics are similarly predicated on their individual moral beliefs. Consequently, the conclusions obtained from their framework are also derived from their individual beliefs, and have no claim to being objective.